Hubungan Pengendalian Diabetes Melitus Type 2 Dengan Kejadian Retinopati Diabetes Di Rsud Dr Chasan Boesoirie Ternate - Eko Sudarmo Dahad Prihanto; Yetrina Yetrina; Muhammad Sultan Firman Syah; Andri W Johan Imbar (Jurnal Health Sains, 2022)
Background: Controlling type 2 diabetes mellitus (DMT2) is very important in reducing the possibility of complications. The incidence of complications of DMT2 includes macrovascular and microvascular. An important microvascular complication is diabetic retinopathy, which is strongly influenced by the duration of diabetes, hyperglycemia and hypertension. Many studies with mixed results regarding the relationship of controlled diabetes with the incidence of diabetic retinopathy. Purpose: This study aims to determine the relationship between T2DM control and the incidence of diabetic retinopathy at Dr Chasan Boesoirie Hospital Ternate. Methods: This study used an analytic observation design with a cross sectional approach. DMT2 patients who visit the internal medicine polyclinic are examined for HbA1c and examined by an ophthalmologist to diagnose the presence or absence of diabetic retinopathy. Samples were taken by purposive sampling. Correlation test analysis was carried out with the Chi Square test. Results: In DMT2 who visited the Internal Medicine Polyclinic at Dr. Chasan Boesoirie found. Conclusion: There is a non-significant relationship with p=0.179 between controlled T2DM and the incidence of diabetic retinopathy. Early detection of diabetic retinopathy is required by funduscopic examination with regard to the status of T2DM control